Identification of Culex complex species using SNP markers based on high‐resolution melting analysis. (26th February 2013) - Kang, David; Sim, Cheolho
Abstract: Mosquitoes belonging to the Culex pipiens complex are primary vectors for diseases such as West Nile encephalitis, Eastern equine encephalitis, many arboviruses, as well as lymphatic filariases. Despite sharing physiological characteristics, each mosquito species within the Culex complex has unique behavioural and reproductive traits that necessitate a proper method of identification. Unfortunately, morphometric methods of distinguishing members of this complex have failed to yield consistent results, giving rise to the need for molecular methods of identification. In this study, we propose a novel identification method using high‐resolution melting (HRM) analysis by examining single‐nucleotide polymorphisms in the acetylcholinesterase‐2 ( ace‐2) locus. Our method provides a high confidence for species determination among the three Culex complex mosquitoes.